Effectiveness of using rubber bumper and restrainer on mitigating pounding and unseating damage of bridge structures subjected to spatially varying ground motions - Shrestha, B.; Hao, Hong; Bi, Kaiming (Pergamon, 2014)
Pounding and unseating damages to bridge decks have been observed in almost all the previous major earthquakes. Recent studies have highlighted that adjusting the fundamental periods of adjacent structural elements close to each other, the only method suggested by the codes to mitigate pounding and unseating damage, is not sufficient to prevent such damages owing to the relative displacement induced by spatially varying ground motions. As pounding and unseating damage could lead to significant loss of economy and life owing to inability to quickly access the damaged area immediately after an earthquake, it is important to protect lifeline bridge structures. Past earthquakes have revealed that the commonly used steel cable restrainers have limited effectiveness. Additionally, only limited research has focused on mitigating pounding forces on the bridge joints that lead to localized damages and disruptions of the serviceability of the bridge after strong shakings. This study presents an extensive investigation on the effectiveness of combining rubber bumpers as a shock absorbing device along with Shape Memory Alloy (SMA) or steel cable restrainers to mitigate pounding and unseating damages on multiple-span bridges subjected to spatially varying ground motions. The responses of bridge structures with different restraining devices acting alone and in combination with rubber bumpers subjected spatially varyingground motions are compared and discussed. The result indicates that the SMA restrainers combined with rubber bumpers could lead to better performance in terms of reduction of joint opening and mitigation of large pounding forces.